Adult HIV/AIDS patients are more likely to experience anxiety symptoms - Abdu, Zakir; Belayneh, Wondwossen; Dule, Aman; Alemu, Solomon Seyife; Wedajo, Lema Fikadu; Hajure, Mohammedamin; Tesfaye, Gebremeskel Mulatu; Workneh, Yadeta Alemayehu; Gezimu, Wubishet; Adem Hussen, Mustefa; Tefera, Bilisumamulifna; Habib, Sadik (Frontiers in Psychiatry, 2025)
BackgroundAmong various mental disorders, anxiety disorder is commonly reported in HIV-positive individuals. Compared to the general population, people living with HIV/AIDS exhibit a higher prevalence of anxiety, with an estimated figure of 68.2% versus 29% in the general population. However, there is a scarcity of studies on the prevalence and associated factors of anxiety among people living with HIV/AIDS in Ethiopia.MethodAn institution-based cross-sectional study was conducted among 320 participants at Gambella General Hospital. The Beck Anxiety Inventory (BAI) scale, Fagerström Test for Nicotine Dependence (FTND), Severity of Dependence Scale (SDS), and the Alcohol Use Disorder Identification Test (AUDIT) were used to collect the data. Data analysis was performed using SPSS version 25. Bivariate and multivariable logistic regressions were employed to identify independently associated variables, and statistical significance was determined at a p-value <0.05.ResultsOut of a total of 323 samples, 320 respondents completed all items, resulting in a response rate of 99.07%. The results showed that 28.4% (95% CI = 23.2–33.9) of participants had anxiety. Factors such as being aged 25 to 40 years, having seen a counselor, HIV disclosure, alcohol use disorders, and perceived high stigma were significantly associated with anxiety in people living with HIV (PLWH).ConclusionIn the study area, about two out of every seven people living with HIV/AIDS experienced anxiety symptoms. Factors such as being aged 25 to 40 years, having seen a counselor, HIV disclosure, alcohol use disorders, and perceived high stigma were significantly associated with anxiety in this population. Based on these findings, timely intervention is recommended to enhance the overall well-being and quality of life for people living with HIV (PLWH), leading to better health outcomes, reducing the burden of mental health issues, and supporting more holistic, patient-centered care.